Strength of gas tungsten arc welding joint - Mohd Nor Ridzuan, Jamaludin (2007)
Welder that involve in small business obviously not using gas tungsten arc welding because of the high cost. This welding is suitable for materials that have a high ability of strength. This welding often use in heavy and middle industry and the strength of the welding joint is proven by the majority of the heavy industry like piping. The advantage of using gas tungsten arc welding are the strength and do not have to use the grinder because the surface of the weld is already smooth. Skill and technique of handle the current and material that used to this welding is very useful because it complex than others. Stainless steel and mild steel is used in this project and the material is weld in tee joint. butt joint and lan joint. To test the joining that been weld. instron tensile machine is used. The study shows that stainless steel that use lan joint has a maximum strength that is 0.97255 MPa. The study also show that the joint is effect the strength of the weidin. and foi that the suitable joint that use is lan joint.